Traffic management project in Phnom Penh. (December 2018) - Matsuoka, Seiya
Abstract: Traffic congestion and accidents are major issues in Phnom Penh, the capital city of the Kingdom of Cambodia. An inefficient signal system and lack of traffic discipline contributed to the unfavorable traffic conditions. A comprehensive traffic management project was recently implemented. An area traffic control system that controls traffic signals in the city based on the traffic conditions was introduced, and other traffic management improvement works such as pavement markings, traffic signs, and median dividers were installed. The project is making a positive impact on road users. Efficient operation and maintenance are key factors for the project to sustain its benefits. Highlights: Traffic in Phnom Penh was not in good condition before this project An area traffic control system that controls all signals in the city from the center was introduced Traffic management measures (traffic sign, pavement marking, etc.) were undertaken Adequate operation and maintenance are key for the benefits to continue